QUANTITATIVE ASSESSMENT OF THE TECHNICAL AND TECHNOLOGICAL PARAMETERS OF THE RAILWAY STATIONS ON THE BASIS OF ERGATIC MODELS - Bobrovskyi, V. I.; Vernyhora, R. V.; Malashkin, V. V. (Science and Transport Progress, 2007)
The report is devoted to a problem of choice of the most effective measure complex for perfection of technical and technological parameters of stations. For the decision of this problem it is offered to use simulation models and methods of vectorial optimization.